PSA campaign outline / Norsharina Samsuri - Samsuri, Norsharina (Faculty of Art and Design, Universiti Teknologi MARA Melaka, Alor Gajah Campus, 2014)
Be specific with target should be specifically defined as demo/ the personal of the ad and the audiences more likely respond to reply on psycho * Be specific Focus on targeting an audience the campaign. It is also to identify graphy should be specifically defined as with target relatively group acceptance to be demo/ the personal of the ad and the audiences influenced, and to consider what psycho more likely respond to reply on would be the main focus to change. the campaign. It is also to identify relatively group acceptance to be graphy influenced, and to consider what would be the main focus to change. * To grab attention from audience to Appropriate in qualitative notice the ad, the message must be USP * Appropriate in remained in the mind of the viewer. To grab attention from audience to notice the ad, the message must be features. It depends on the appropriate type USP ad qualitative remained in the mind of the viewer. ad It depends on the appropriate type features. of appeal applied, with the message ad + idea- well delivered, easy to understand cate- ad of appeal applied, with the message gories + well delivered, easy to understand and relevant to the audience. cate- idea- tion The technique’s selection and tactic gories tion and relevant to the audience. The technique’s selection and tactic in creating creative execution of the in creating creative execution of the message are also important factors ESP ESP message are also important factors in developing an advertising in developing an advertising campaign. campaign. AD AD CATE- + IDEA- GORIES TION AD AD CATE- + IDEA- GORIES TION demo/ design psycho execution graphy demo/ design psycho execution graphy